BACTERIAL CAUSES AND ANTIMICROBIAL SENSITIVITY PATTERN OF EXTERNAL OCULAR INFECTIONS IN SELECTED OPHTHALMOLOGY CLINICS IN SANA’A CITY - Alshamahi, Essam Yahya A; Al-Shamahy, Hassan A.; Musawa, Yaser Ali; Al-Shami, Huda Zaid (Universal Journal of Pharmaceutical Research, 2020)
Objectives: The aim of the current study was to reveal the bacterial profile and pattern of sensitivity to antibiotics for external ocular infections for patients who attended selected ophthalmology clinics in the city of Sana’a. Methods: A cross-sectional study design was used from September 2016 to October 2017 where a total of 197 patients with infection of external eye were included in the study which included conjunctivitis, keratitis, blepharitis and Blepharoconjunctivitis. Samples were collected and transferred to the National Center of Public Laboratories (NCPHL), in Sana'a. Possible bacterial pathogens have been isolated and identified using regular laboratory techniques, and microbial sensitivity testing has been carried out using a disc diffusion method. Results: A total of 197 ocular samples were obtained for microbiological evaluation, of these 146 (74.1%) have bacterial growth. Bacteria of Gram positive accounted for 52.1% and the prevalent isolation was S. aureus (30.1%). Gram negative bacteria made up 47.9% and the predominant isolation was Pseudomonas aeruginosa (26.7%). The majority of Gram-positive bacteria were sensitive to ciprofloxacin (90% - 100%), vancomycin (86% - 100%) and Gram-negative isolates sensitive for amikacin (100%) and ciprofloxacin (63% - 100%). Conclusion: These results revealed that Gram-positive bacteria were the generally common bacteria isolated from infections of external eye and were more susceptible to vancomycin and ciprofloxacin while Gram-negative isolates were more susceptible to ciprofloxacin and amikacin. The high rate of resistance for most antibiotics in Yemen, leaves ophthalmologists with very few options of drugs to treat eye infections. Large-scale ongoing studies in the future should also be conducted in order to monitor the antimicrobial resistance of the external ocular bacterial isolates. Peer Review History: Received 2 April 2020; Revised 11 May; Accepted 26 June; Available online 15 July 2020 Academic Editor: Dr. Asia Selman Abdullah , Al-Razi university, Department of Pharmacy, Yemen, asia_abdullah65@yahoo.com Reviewer(s) detail: Dr. Jucimary Vieira dos Santos , Hemonorte Dalton Barbosa Cunha, Brazil, jucimaryvieira@yahoo.com.br Dr. Sabah Hussien El-Ghaiesh , Tanta University, Egypt, s.ghaiesh@gmail.com